Narasimha depicted in a dancing stance - Temples of India Project Team (Jio Institute, 2024)
This is a fascinating and rare image of Narasimha depicted in a dancing stance. He stands on one foot placed over what appears to be a prostrating figure, possibly a woman. With one hand raised in the air, he forms a lap above which the slain demon king is placed. He has eight arms and is accompanied by a dwarf warrior whose dynamic movement complements the dynamic posture of Narasimha. Such an iconographic depiction of Narasimha is rare and the identity of the dwarf warrior and the prostrating figure over which he stands remain enigmatic.